Osmosis And Dealing With Toxicity In The Prophetic Medicine - Sami Khalaf Salim Al Bzeirat; Mahmoud Mohamed Ali Mahmoud Edris; Mahmoud Mohamed Ali Mahmoud Edris; Abdul Manan Ismail; Farah Salwani Muda @ Ismail (USIM Press, 2024)
Non-Indexed Publication